Emerging Concepts in Carbon Nitride Organic Photocatalysis. Issue 11 (20th November 2020) - Mazzanti, Stefano; Savateev, Aleksandr
Abstract: Carbon nitrides encompass a class of transition‐metal‐free materials possessing numerous advantages such as low cost (few Euros per gram), high chemical stability, broad tunability of redox potentials and optical bandgap, recyclability, and a high absorption coefficient (>10 5  cm −1 ), which make them highly attractive for application in photoredox catalysis. In this Review, we classify carbon nitrides based on their unique properties, structure, and redox potentials. We summarize recently emerging concepts in heterogeneous carbon nitride photocatalysis, with an emphasis on the synthesis of organic compounds: 1) Illumination‐Driven Electron Accumulation in Semiconductors and Exploitation (IDEASE); 2) singlet‐triplet intersystem crossing in carbon nitride excited states and related energy transfer; 3) architectures of flow photoreactors; and 4) dual metal/carbon nitride photocatalysis. The objective of this Review is to provide a detailed overview regarding innovative research in carbon nitride photocatalysis focusing on these topics. Abstract : Carbon nitrides are distinguished as transition‐metal‐free photocatalysts. Their chemical and thermal stability, combined with a low cost of production makes them very popular in the field of photocatalysis. This Review summarizes recent and emerging concepts in carbon nitride photocatalysis focused on synthesis of organic compounds.